The Analysis of Online Learning PKN in the Covid-19 Pandemic of SMP Negeri 2 Lintongnihuta Humbang Hasundutan Regency - Melina Melina; Ida Lamtumiur Pasaribu; Leonardo Simanjuntak (Jurnal Mantik, 2021)
This study aims to describe online learning during the Covid19 pandemic as a learning strategy and learning outcomes for eight grade students of SMP Negeri 2 Lintongnihuta. This study uses a qualitative method, the informant of this research is eight grade. The data collection of this research was done through interviews, observation, and documentation. The data analysis technique used is data reduction data compilation and categorization. The results of this study are as follows: (1) Online learning is carried out online by planning and implementing the planning to make evaluation materials and social media while the implementation is to distribute materials and assignments to WhatsApp groups and students who do not have mobile phones take questions to school. The teacher comes to the student's house. In addition, the teacher also makes lesson plans for online learning (2) Learning strategies as online learning plans use learning approaches and models to achieve learning objectives. The approach is to explain the material through videos, students who offline learn the material from the LKS the method is that the teacher makes a video explaining the material and then sends it via WhatsApp. Online is done every day, the collection of assignments is in accordance with the teacher's agreement. The media uses photos or videos, students collect their assignments via a Google form link. The material comes from textbooks and worksheets and is in accordance with basic competencies, and then the teacher makes questions as learning evaluations. (3) student learning outcomes show that not all students can undergo online learning and student learning outcomes are not all achieved due to various factors such as students not having a mobile phone or WhatsApp application, internet signals that are difficult to reach because students' homes are in the village, students' awareness of their responsibilities in doing assignments is still lacking and parental awareness and environmental conditions are less supportive so that student learning outcomes are less than optimal.